Efektifkah Kenaikan Tarif Cukai Rokok Elektrik Cair Sistem Terbuka bagi Industri Rokok Elektrik? - Yunani, Ahmad; Muzdalifah, Muzdalifah; Lestari, Haifa (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2024)
Liquid e-cigarettes have become a popular new form of addictive tobacco products. The increasing prevalence of e-cigarette and smoking behaviors has led the government to increase tobacco tax rates every year. While this policy boosts state revenues, it also poses challenges for conventional and e-cigarette businesses, including tobacco farmers. Excise tariffs for liquid e-cigarettes are divided into open and closed system types, with the method of filling the liquid is the key distinction. Users can manually refill the open system, the closed system cannot be refilled. Despite both containing cigarette liquid, the percentage of raising excise taxes is higher for the open system than the closed system. This study aims to evaluate the effect of the increase of excise taxes on business competition between open and closed systems of liquid e-cigarettes. Using descriptive analysis, literature review, and a basic quantitative approach, this study found that differences in excise tax rates on e-cigarettes encourage competition and create unequal treatments. The higher excise tax on open systems has created a polemic in sustainability of small entrepreneurs in the tobacco sector. The role of the government as a regulator is very important in ensuring fair and responsive policies in order to create conducive business competition between open and closed system liquid e-cigarettes.